Ten years' experience with a pyrocarbon prosthesis replacing the proximal interphalangeal joint. A prospective clinical and radiographic follow-up. (July 2014) - Tägil, M.; Geijer, M.; Abramo, A.; Kopylov, P.
We prospectively assessed the subjective, objective, and radiographic results at 1, 2, and 5 years in 65 patients who had pyrocarbon proximal interphalangeal prostheses inserted between 2001 and 2010. Further operations were done on 10 of the 89 joints (four for prosthetic extraction and arthrodesis, two for component changes, and four for soft tissue procedures). At 1 year, the visual analogue scale score for pain at rest had improved to 0 cm from a pre-operative 4 cm, pain at activity from 6 to 1.8 cm, and Disability of the Arm, Shoulder and Hand score from 40 to 25. Range of movement and grip strength were unchanged. At 5 years, 31 joints (21 patients) had a complete radiographic follow-up. Seven proximal and 12 distal components showing zones of osteolysis at 1 year had stabilized and were inert or integrated at 5 years. Three proximal and three distal components had osteolytic zones at 5 years. Forty-seven of 59 patients were pain-free at rest at 1 year, and 19 of 21 at 5 years. No late revisions or loosening occurred.